The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1991
DOI: 10.1161/01.cir.84.2.503
|View full text |Cite
|
Sign up to set email alerts
|

Left cardiac sympathetic denervation in the therapy of congenital long QT syndrome. A worldwide report.

Abstract: BACKGROUND Long QT syndrome (LQTS) is a congenital disorder accompanied by a high incidence of sudden cardiac death. beta-Adrenergic blockade is the therapy of choice, and it is successful in 75-80% of patients. For those in whom cardiac events (syncope or cardiac arrest) are not prevented by beta-blockade, experimental studies suggest that left cardiac sympathetic denervation (LCSD) may be useful. METHODS AND RESULTS We identified 85 LQTS patients worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
144
0
15

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(164 citation statements)
references
References 49 publications
4
144
0
15
Order By: Relevance
“…10 Importantly for the assessment of the present results, the population under study was at particularly high risk for arrhythmic death, as indicated by the number of symptomatic patients (99%), the high percentage (75%) of those with cardiac events despite ␤-blockers, and the extreme average prolongation of the QT interval (QTc, 543Ϯ65 ms). The last value, which reflects a major arrhythmogenic substrate, 17 should be compared with the mean QTc (QTc, 510Ϯ60 ms) of the largest population in which the effect of ␤-blockers was analyzed.…”
Section: Schwartz Et Al Left Cardiac Sympathetic Denervation and Lqtsmentioning
confidence: 79%
See 1 more Smart Citation
“…10 Importantly for the assessment of the present results, the population under study was at particularly high risk for arrhythmic death, as indicated by the number of symptomatic patients (99%), the high percentage (75%) of those with cardiac events despite ␤-blockers, and the extreme average prolongation of the QT interval (QTc, 543Ϯ65 ms). The last value, which reflects a major arrhythmogenic substrate, 17 should be compared with the mean QTc (QTc, 510Ϯ60 ms) of the largest population in which the effect of ␤-blockers was analyzed.…”
Section: Schwartz Et Al Left Cardiac Sympathetic Denervation and Lqtsmentioning
confidence: 79%
“…Worldwide experience with LCSD in 85 LQTS patients was reported in 1991. 10 Now, 13 years later, we thought it appropriate to review the existing data on 162 patients who underwent left sympathectomy because this large population and the long follow-up permit a more definitive assessment of the role of LCSD in the management of high-risk LQTS patients.…”
mentioning
confidence: 99%
“…Furthermore, epinephrine may induce torsade, whereas left sympathectomy and β-blockers are antiarrhythmic in LQT1. 56,57 These studies suggest that sympathetic activation is arrhythmogenic if I Ks is abnormal or down-regulated. Furthermore, over-expression of NGF in adult transgenic mice results in further decrease in density of at least 2 other potassium currents, I to and I Kur .…”
Section: Myocardial Infarction Heart Failure and Sympathetic Innervmentioning
confidence: 99%
“…[2][3][4] Torsade de pointes associated with the long QT syndrome is often elicited by sudden increases in sympathetic activity 8 and can be suppressed by -adrenergic blocking agents 9 or by ablation of the left stellate ganglion. 10 Isoproterenol infusion prolongs the MAP duration and induces EADs in patients with long QT syndrome. 11 In addition, left stellate stimulation increases the amplitude of EADs induced by Cs and increases the occurrence of ventricular tachycardia (VT) in dogs.…”
mentioning
confidence: 99%